2016
DOI: 10.1128/jvi.00974-16
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus 16 2A Protease Affects Nuclear Localization of 3CD during Infection

Abstract: The human rhinovirus (HRV) 3C and 2A proteases (3C pro and 2A pro , respectively) are critical in HRV infection, as they are required for viral polyprotein processing as well as proteolysing key host factors to facilitate virus replication. Early in infection, 3C pro is present as its precursor 3CD, which, although the mechanism of subcellular targeting is unknown, is found in the nucleus as well as the cytoplasm. In this study, we use transfected and infected cell systems to show that 2A pro activity is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…CLSM and image analysis. Fixed or live (transfected)-cell samples were imaged as described previously (15,47). Digitized fluorescent cell images were collected using a Nikon Ti Eclipse CLSM with a Nikon 60ϫ/1.40 numeric aperture oil immersion lens (Plan Apo VC OFN25 DIC N2; optical section of 0.5 m) and the NIS Elements AR software; data from four individual scans were averaged to obtain the final images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLSM and image analysis. Fixed or live (transfected)-cell samples were imaged as described previously (15,47). Digitized fluorescent cell images were collected using a Nikon Ti Eclipse CLSM with a Nikon 60ϫ/1.40 numeric aperture oil immersion lens (Plan Apo VC OFN25 DIC N2; optical section of 0.5 m) and the NIS Elements AR software; data from four individual scans were averaged to obtain the final images.…”
Section: Discussionmentioning
confidence: 99%
“…Digitized fluorescent cell images were collected using a Nikon Ti Eclipse CLSM with a Nikon 60ϫ/1.40 numeric aperture oil immersion lens (Plan Apo VC OFN25 DIC N2; optical section of 0.5 m) and the NIS Elements AR software; data from four individual scans were averaged to obtain the final images. Digital images were analyzed as described previously using ImageJ software to determine the fluorescence intensity above background (Fb) in the nucleus (Fn) compared to that in the cytoplasm (c) and to determine the nuclear-to-cytoplasmic fluorescence ratio (Fn/c) (47).…”
Section: Discussionmentioning
confidence: 99%
“…These activities are thought to influence host immune response signaling for which cytosolnucleus communication and trafficking is essential. It recently became clear that rhinovirus 2A protease activity also plays a role in targeting rhinovirus 3C protein to the nucleus [113,114], however, it is not clear what 3C protease is doing there exactly [114,115].…”
Section: Respiratory Virus Proteases Cleaving Cellular (Innate Immunementioning
confidence: 99%
“…Interestingly, the viral protease is located early after infection (8 hrs for DENV and 12 hrs for ZIKV) in the perinuclear region as well as in the nucleus of the cells and at 24 hpi the protein is present in the cytoplasm in the perinuclear region. Degradation of nucleoporins by the activity of viral proteases located in the perinuclear region, such as the 2A protease from poliovirus, or in the nucleus such as the 3CD protease-polymerase from rhinovirus 35,36 have been reported, suggesting that NS3 located in this two particular locations could reach and cut its target NUPs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that degradation of nucleoporins occurs by the activity of viral proteases located in the perinuclear and the nuclear regions, such as the 2A and 3CD from rhinovirus 35,36 . Nup98 is degraded early after DENV and ZIKV infection and it is located in both the nuclear and the cytoplasmic regions of the NPC; thus, it is possible that its degradation may be mediated by the protease present in the perinuclear region or in the nucleus of the infected cells.…”
Section: Ns3 Localizes In the Perinuclear Region And In The Nucleus Omentioning
confidence: 99%